Hair and Scalp Disorders 2017
DOI: 10.5772/67379
|View full text |Cite
|
Sign up to set email alerts
|

Hair Loss in Children, Etiologies, and Treatment

Abstract: Hair loss in children is a common and important complaint in dermatology and pediatric clinics and can be considered as a difficult and challenging problem in some cases. Early management is needed as this has its effect on development of normal mental and physical growth of children. Alopecia or hair loss is of particular concern in pediatric group, as it is associated with more significant psychological consequences in this growing age group and has patterns that are different from that seen in adults. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…8 Penyakit ini dapat menimbulkan rasa cemas orang tua ataupun anak. 9 Selain itu, diagnosis kadang kala menjadi tantangan, mengingat kondisi alopesia non-sikatrisial pada anak tidak hanya akibat AA saja. 10 Diagnosis dan manajemen yang tepat penting karena dapat memengaruhi perkembangan psikososial anak.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…8 Penyakit ini dapat menimbulkan rasa cemas orang tua ataupun anak. 9 Selain itu, diagnosis kadang kala menjadi tantangan, mengingat kondisi alopesia non-sikatrisial pada anak tidak hanya akibat AA saja. 10 Diagnosis dan manajemen yang tepat penting karena dapat memengaruhi perkembangan psikososial anak.…”
Section: Pendahuluanunclassified
“…10 Diagnosis dan manajemen yang tepat penting karena dapat memengaruhi perkembangan psikososial anak. 9 Kami melaporkan 5 kasus AA berusia di bawah 18 tahun. Pembahasan terutama pada diagnosis AA, baik melalui pemeriksaan klinis maupun pemeriksaan penunjang.…”
Section: Pendahuluanunclassified
“…Adolescent men's vellus hair changes into terminal hair due to hormones. This operation is visible on his beard, armpits, chest, and genitalia A [7].In addition to being a sign of overall physical health, women may flaunt their confidence, attractiveness, and power when their hair is in good condition. This is why women are more likely than males to experience psychological issues related to hair loss [8].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of FPHL varies among population groups and increases with age [5]. Mostly, women visit a dermatologist for hair loss, due to its effect on their cosmetic appeal [6].…”
Section: Introductionmentioning
confidence: 99%
“…Up to my knowledge no study has been conducted in our region as well as South Asia. After extensive research, only 2, 3 studieswere found which were done in Eastern Europe and Egypt by Moneib H, & Fathy G, Ouda A et al [6,12] The aim of this study was to shed light on this territory through estimating the status of vitamin D in female patients with FPHL. Low serum 25 OH vitamin D3 is associated with hair loss in females with FPHL.…”
Section: Introductionmentioning
confidence: 99%